Netizens’ comments on “Ice Cold” murder documentary: A thematic analysis of Corbuzier’s podcast - Mulyono, Annastasya Meyzsa; Bhakti, Aditya Dwi Putra (Universitas Padjadjaran, 2025)
Background: The cyanide coffee case resurfaces public attention after the release of the documentary film “Ice Cold: Murder, Coffee and Jessica Wongso” by Netflix. The famous Indonesian podcaster, Deddy Corbuzier, raises this issue in his content. This leads to reactions and debate among netizens. Netizens expressed their opinions through the comments column on Deddy Corbuzier’s YouTube account. Purpose: This research aimed to explore the diversity of netizens’ comments on Deddy Corbuzier’s YouTube podcast videos through thematic analysis. Methods: This research used a qualitative approach with an interpretive research type. The data analysis technique used was Virginia and Clarke’s thematic analysis. This research discussed Quiring and Schweiger’s interactivity and Robert Plutchik’s theory of emotion. Results: The research results describe netizens’ responses to Deddy Corbuzier’s YouTube video on the issue of suspect Jessica for the murder of Mirna. The results were divided into two: initial thematic and final thematic. Conclusion: The findings on the final theme were grouped into four sub-themes, divided into two categories for Jessica’s innocence by misunderstanding the judge’s decision and supporting the reopening of the case. The second category is guilty based on netizens’ perceptions of Jessica’s supporters and agreeing with the judge’s decision. Implications: This research examines messages and interactions among netizens towards Jessica from the influence of the Documentary Film “Ice Cold: Murder, Coffee and Jessica Wongso” by Netflix on Deddy Corbuzier’s podcast. It reflects the perspectives and preferences in society towards the film.